In vitro expression of enolase from Streptococcus suis serotype 2 and it’s antigenicity - Hoang Bach Nguyen; Thi Dang Khoa Nguyen; Gessica Tore; Van An Le; Alberto Alberti (Vietnam Journal of Science, Technology and Engineering, 2018)
Streptococcus suis serotype 2 (SS2) is one of the most important pathogens in the porcine industry and an important zoonotic agent. The absence of suitable vaccine or virulence markers makes SS2 infections more difficult to control. An immunoproteomics approach is used for identifying antigenic proteins in SS2 recognized enolase, which may represent strainspecific antigenic proteins and potential protective antigens. This study aims to clone, express enolase gene from SS2 and use western blotting to evaluate the antigenicity. Enolase gene from the SS2 strain was amplified with specific primers. The obtained PCR product was inserted into an expression vector, pGEX- 4T1. The recombinant vector was then transformed into BL21 cells for protein expression. Subsequently, the immunological activity of the recombinant enolase was tested by western blotting with human sera in the convalescent phase. The glutathione S-transferase (GST)-tag fusion enolase was purified by glutathione sepharose affinity chromatography for further studies. The SS2 recombinant enolase was successfully expressed in E. coli. The western blotting analysis demonstrated that enolase has an antigenic property, which is recognized by patients naturally infected with SS2.